Effects of pertussis toxin and Bordetella pertussis lipo-oligosaccharide on the specific toxicity and potency of whole-cell pertussis vaccines - I. A. Alekseeva; I. V. Ibragimkhalilova; D. N. Lepekhova (Биопрепараты: Профилактика, диагностика, лечение, 2023)
Scientific relevance. The content of Bordetella pertussis lipo-oligosaccharide (LOS) and the residual levels of active pertussis toxin (PT) are generally accepted to be the primary factors that determine the reactogenicity of whole-cell pertussis vaccines. To improve the quality of whole-cell pertussis vaccines, it is both relevant and necessary to study the relationship between the toxicity of B. pertussis bacterial cell components and the main quality parameters of these vaccines, including their potency and specific toxicity, as termed in the WHO recommendations and the European Pharmacopoeia.Aim. This study aimed to analyse the effects of B. pertussis LOS and residual active PT on the specific toxicity and potency of adsorbed diphtheria, tetanus, and whole-cell pertussis (DTwP) vaccines.Materials and methods. The authors tested 57 commercial batches of adsorbed DTwP vaccines for compliance with the regulatory standards and product specification files. Vaccine batches that failed specific toxicity tests formed Group 1, and the other batches were designated as Group 2. The potency was tested in F1 CBA/Ca×C57BL/6J hybrid mice with experimentally induced meningoencephalitis that were immunised with DTwP and reference vaccines. The authors assessed the specific toxicity of DTwP vaccines by changes in body weight following intraperitoneal administration. The toxic activity was assessed indirectly by changes in body weight in the first 16–24 h (B. pertussis LOS) and on day 7 (PT) after dosing. The authors used Spearman’s rank correlation coefficient to measure the strength of correlation between the toxic activity of vaccine components and the specific toxicity and potency of the vaccine, which were established using the same vaccine batches.Results. The authors measured the toxic activity of LOS and residual active PT in the vaccine batches studied. The correlation coefficients between the specific toxicity and potency of the vaccines and the toxic activity of LOS were 0.113 (p>0.05) and 0.049 (p>0.05), respectively. Similarly, the correlation coefficients between the specific toxicity and potency of the vaccines and the toxic activity of PT accounted for 0.595 (p<0.01) and –0.534 (p<0.01), respectively.Conclusions. The authors studied the toxic activity of B. pertussis LOS and residual active PT in whole-cell pertussis vaccines and found an inverse correlation between the potency of the vaccines and the toxic activity of residual active PT. The study demonstrated that the specific toxicity test for whole-cell pertussis vaccines fails to detect and quantify B. pertussis LOS in the samples. The authors advise to determine the content of LOS in the B. pertussis strains intended for the production of whole-cell pertussis vaccines, which is not yet an accepted practice in the Russian Federation.